Implementation of Law on Freedom of Expression in the Digital Era: Perspective of Law Number 19 of 2016 - Shela Agnesia Shelvira; Siti Nur Ajijah; Moch Rifat Novri Mulyana; Lucky Hakim; M Algi Fahril; Dedi Mulyadi (Al-Musthalah: Jurnal Riset dan Penelitian Multidisiplin, 2024)
In the increasingly advanced Digital Era, social media has become an important platform for people to communicate, share information and express themselves. The platform provides a space for individuals to build an online identity, connect with others, and engage in various communities. Expression on social media varies greatly and is influenced by many factors, including culture, education, social environment, and technology. This journal focuses on the application of law to freedom of expression in the digital era, referring to the perspective of Law Number 19 concerning Information and Electronics (UU ITE). The method used in this research uses a formative juridical method, namely the preparation and application of law in a structured and systematic manner using clear and simple language and the use of case examples. Although social media provides many benefits, there are risks and challenges associated with self-expression such as; Cyberbullying, Harassment, Hoaxes and one of them is Defamation.